The E6 protein from vaccinia virus is required for the formation of immature virions - Boyd, Olga (2010)
An IPTG-inducible mutant in the E6R gene of vaccinia virus was used to study the role of the E6 virion core protein in viral replication. In the absence of the inducer, the mutant exhibited a normal pattern DNA replication, concatemer resolution and late gene expression, but it showed an inhibition of virion structural protein processing it failed to produce infectious particles. Electron microscopic analysis showed that in the absence of IPTG viral morphogenesis was arrested before IV formation: crescents, aberrant or empty IV-like structures, and large aggregated virosomes were observed throughout the cytoplasm. The addition of IPTG to release a twelve-hour block showed that virus infectious particles could be formed in the absence of de novo DNA synthesis. Our observations show that in the absence of E6 the association of viroplasm with viral membrane crescents is impaired.